The Influence of Managerial Ownership, Institutional Ownership and Debt Policy on Company Value - Senni Mawar J Sihombing; Arif Makhsun; Irawan Irawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
In today's competitive economic environment, increasing a company's value is essential for staying afloat, drawing in investors and proving that management is up to the task. A company's high or low value is heavily influenced by factors such as management ownership, institutional ownership, and debt policy, all of which aim to enhance firm value. Managerial, institutional, and debt policy ownership's impact on business value is the intended focus of this research. This research makes use of secondary data collected through purposive sampling. The study's findings indicate that, first, firm value is negatively impacted by managerial ownership, second, firm value is unaffected by institutional ownership, third, firm value is positively impacted by debt policy, and fourth, the sector's capital structure is affected by all three factors at once.